[OA258] Handheld MED testers: An inter-comparison to inform requirements for acceptance testing and calibration. (August 2018) - Manley, Michael; McCavana, Jackie
Abstract : Purpose: Hand held Minimal Erythema Dose (MED) testers are designed to measure the MED for a patient receiving UVB phototherapy. The devices have a series of apertures with a superimposed foil grid of varying attenuation so that 10 incremental doses of UVB are delivered to a patient simultaneously. Introducing these devices into clinical service has presented challenges from a validation and output measurement perspective because of the device's aperture size, the smaller bulb size, exposure geometry (device is in contact with the patient's skin) and warm up characteristics of the bulb. In this study an inter-comparison is 'performed on a number of units/models, to evaluate their performance characteristics and determine the minimum testing required before introducing such units into clinical service. Methods: A piece of EBT3 Gafchromic film calibrated to UVB dose was placed on device exposure area and was used to measure both the absolute and relative output of the apertures of each device. A four minute exposure was acquired after the warm up time specified by the manufacturer. This measurement was repeated for a 20 min exposure from switch on with no warm-up. The output characteristics were compared to manufacturer's specification and an inter comparison was carried out between same model devices. Warm up and spectral characteristics of each device were also measured using a spectral radiometer. Results: Outputs measured were within 13% of that quoted by the manufacturer at the specified warm up time. Results show that the measured relative outputs agreed with that of the manufacturer within 15% and range of relative outputs for a number of units of the same model spanned over a range of up to 30%. Conclusions: Minimum acceptance testing of such units should include evaluation of warm-up characteristics; and simultaneous output measurements of all apertures over patient exposure time interval. This will allow a table of planned aperture exposures to be confirmed/determined. Periodic output measurement can then be carried out with EBT3 Gafchromic film or radiometer that has a detector with a suitable sized input optic.